Corporate Governance and Sustainability Report Disclosure in Healthcare Companies: The Moderating Role of Profitability - Aisyah Juliana; Herlin Tundjung Setijaningsih (Academic Bright Collaboration, 2025)
This study aims to examine the influence of corporate governance mechanisms on sustainability report disclosure in healthcare companies listed on the Indonesia Stock Exchange during the period 2021 to 2024 and to analyze the moderating role of profitability in these relationships. The research addresses the growing demand for environmental, social, and governance transparency and the need to understand how governance structures contribute to credible sustainability disclosure in a sector that generates significant environmental externalities. The study adopts a quantitative explanatory design using secondary data derived from annual reports and sustainability reports of healthcare companies. A purposive sampling technique resulted in a final sample of 20 firms with 80 firm year observations. Sustainability disclosure is measured using the Sustainability Report Disclosure Index based on the Global Reporting Initiative standards, while corporate governance variables include managerial ownership, independent commissioners, audit committee size, and institutional ownership. The data are analyzed using panel data regression with the Fixed Effect Model and Moderated Regression Analysis to test the moderating effect of profitability measured by return on assets. The results indicate that audit committees and institutional ownership have a significant positive effect on sustainability disclosure, while managerial ownership and independent commissioners do not show significant direct effects. Profitability significantly strengthens the relationship between managerial ownership and sustainability disclosure as well as between institutional ownership and sustainability disclosure, but does not moderate the influence of board level governance mechanisms. The findings are limited to healthcare companies in Indonesia and rely on disclosure indices derived from corporate reports, which may affect generalizability and measurement depth. This study contributes to the literature by extending agency theory in the context of sustainability governance and provides practical implications for corporate managers, regulators, and investors in strengthening governance mechanisms to improve sustainability transparency.